Підвищення енергетичної ефективності системи теплозабезпечення міст України як основний фактор впливу на її сталий розвиток - Тормосов, Р. Ю. (Ways to Improve Construction Efficiency, 2012)
In the article is grounded the increase of energy efficiency of the Ukraine cities heat supply system as bases for strengthening its national safety and important factor of influence on its stable development.